O AVESSO: alcances e limites da consultoria em design na Associação de Mulheres da Agulha Criativa, em São João dos Patos - MA. - LIMA, MÁRCIO SOARES (2018)
This research is intended to identify and analyze the effects of design consulting in the Associação de Mulheres da Agulha Criativa – AMAC, stemming from the discourses and practices of artisans and designers. We consider essential to this work the Virtuous Ladder of Design and Development, introduced by Gabriel Patrocínio (2015), in which we interpret, from the context of this research, the performance of the design consultant in several steps of the ladder and its relation to the artisans; the approaches of Adélia Borges (2011) and Zoy Anastassakis (2014) pointed out a panorama of the relationship between design and handycraft in Brazil; Kubrusly and Imbroisi (2011), dealing with design consultancies in artisan communities; and Escobar (2016), problematizing the development brought by the virtuous scale and by SEBRAE, in addition to other important contributions that have helped us to reflect on these themes. The research was characterized as exploratory and descriptive, based on a case study. We used as methodological tools, focus group, semi-structured interviews, and field observation. In the finishing touches of this research, we therefore perceive the limits of the design consultancy at AMAC. These limits and scope between designers and craftsmen, which we present in the title of this research, are based on the idea of uninvolvement, which means taking a step back from a creative capacity, within a specific time frame, in favor of productivity. At each item analyzed in chapter four, we perceive new elements coming up, new stories being told and their various versions, and new meanings started appearing. But at the same time we realize that the vitality of these observations goes along the same path of the craftsmanship, culture and events here reported: slow and full of variables. The context of this work may resemble many others throughout the country, so we assume that our closing is not final, but temporary, and from now on future research is advisable.